Xanthogranulomatous salpingo-oophoritis mimicking an ovarian malignancy: a clinical dilemma - Farooq, Summiya; Abbas, Farhat; Abbas, Rahat; Beigh, Ambreen; Reshi, Ruby; Khuroo, Mehnaaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Xanthogranulomatoussalpingo-oophoritis is an uncommon form of chronic inflammation in the genitourinary tract. Its symptoms and radiological findings mimic ovarian malignancy. Aim of this study was to evaluate the clinicopathological pattern of xanthogranulomatous salphingo oophoritis. Methods: This study was conducted in the department of pathology, Government Medical College, Srinagar. It was a retrospective study done over a period of 5 years, November 2014 to November 2019. Results: The study was done to evaluate the clinicopathological pattern of 6 cases of rare entity xantogranulomatous salphingo oophoritis diagnosed at a tertiary care hospital. All patients, presented with pain abdomen. All patients were operated due to radiological suspicion of ovarian malignancy. Histopathological examination proved the lesion as xanthogranulomatous salphingo oophoritis. Conclusions: Xanthogranulomatoussalpingo-oophoritis is a rare condition that is often mistaken for ovarian malignancy clinically and radiologically. Oophorectomy is the recommended treatment but most women are “over treated” with staging laparotomies and hysterectomies that render them infertile.